Hydrological sensitivity affected by tropical tropospheric stability - Lee,D; Ceppi,P (2025)
Climate forcers perturb the energy amount inside the Earth, and atmospheric interactions in the troposphere sequentially vary to pursue the new stable state in the given energy budget. The varied energy amount of longwave, shortwave, and sensible heat flux in the atmosphere is balanced with latent heat flux, equivalent to the changes in precipitation in the global mean sense. For example, rising temperature emits more longwave radiation from the atmosphere (longwave cooling, LWC), and it allows more energy budget room for latent heat flux (LHF) heating, which explains enhanced precipitation.Although previous studies argued hydrological sensitivity as the linearized scale of precipitation change per the global mean temperature change, this study confirms that tropical tropospheric stability has additionally affected hydrological sensitivity over the decades. Our results reveal that tropical ocean temperature patterns correlate statistically with the stability index. The numerically simplified term of this stability effect improves the prediction skills of the theoretical equation for the global mean precipitation change under scenarios with various forcing conditions. Lastly, we discuss the possible impacts of recent ocean patterns and the tropical tropospheric stability phase on precipitation by comparing the observed data and climate models’ simulations, which are forced by the observed sea surface temperature.